Lethal pathogens, non-lethal synergists and the evolutionary ecology of resistance. - Bonsall, M; Raymond, B (2008)
Mixed pathogenic infections are known to have profound effects on the ecological and evolutionary diversity of both hosts and parasites. Although a variety of mechanisms have been proposed by which hosts can withstand parasitic infections, the role of multiple infections and the trade-off in multiple defence strategies remain relatively unexplored. We develop a stage-structured host-pathogen model to explore the ecological and evolutionary dynamics of host resistance to different modes of infection. In particular, we investigate how the evolution of resistance is influenced through infection by a lethal pathogen and a non-lethal synergist (that only acts to enhance the infectivity of the pathogen). We extend our theoretical framework to explore how trade-offs in the ability to withstand infection by the lethal pathogen and the ability to tolerate the synergist affect the likelihood of coexistence and the evolution of polymorphic host strategies. We show how the underlying structure of the trade-off surface is crucial in the maintenance of resistance polymorphisms. Further, depending on the shape of the trade-off surface, we predict that different levels of host resistance will show individual responses to the presence of non-lethal synergists. Our results are discussed in the wider context of recent developments in understanding the evolution of resistance to pathogen infections and resistance management.